Development and Performance Test of Vertical Stirrer Rotary Blade Type of Sago Starch Extraction Machine Powered by Gasoline Engine - Darma Darma; Reniana Reniana; Risma Uli Situngkir; Arens T. Solissa (Jurnal Natural, 2026)
Sago starch extraction is aimed to separate starch as much as possible from waste or fibre. The efficiency and effectiveness of extraction process depend on several factors i.e. the characteristics of extraction machine and fineness degree of disintegrated sago pith is being processed. In previously study, it had been resulted stirrer rotary blade type of sago starch extraction machine powered by gasoline engine. The purpose of this study was to develop and test the performances of stirrer rotary blade type of sago starch extractor. The developed machine was tested it’s performances under 4 levels of extraction duration time i.e. 10 minutes, 15 minutes, 20 minutes and 25 minutes. The Parameter have been measured to evaluate the machine’s performances were (1) extraction capacity, (2) starch rendement, (3) starch yield and (4) starch losses in sago pith waste. Based on performance test results have shown that the developed machine has higher performance than previously prototype. The results showed that extraction duration time significantly affect extraction capacity, starch rendement, and starch losses in sago pith waste, however the starch yield was not affected significantly. The highest performance was resulted at extraction duration time 15 minutes. The performances of the machine at the condition were (1) extraction capacity 247 kg repos/hour, (2) starch rendemen 37,35%, (3) starch yield 78,81 kg/hour, and (4) starch losses in sago pith waste 2,00%.